GOVERNMENTAL ACCOUNTING IN THE EDUCATION OF THE PUBLIC ACCOUNTANT. - Hackett, Robert P. (The Accounting Review, 1938)
There is probably no field of accounting in which a greater opportunity for missionary work exists. The field of governmental accounting has received as little recognition as any, but the education of those who will keep the records cannot go far until those who arc to install and audit the records understand the proper procedures to follow. The governmental units have a larger dollar volume than any other industry but there is probably no industry in which less adequate accounting systems may be found. The increasing scope of public business in municipal, state, and Federal governments should be recognized. The accountant will be looked to as the one who can meet this situation, but if his training has included nothing on this special problem he will not be ready. It may be that the failure to give more importance to governmental accounting is attributable to the lack of a widespread offering in colleges and universities comparable to other accounting subjects. Education for the aspiring accountant should not be measured by what is available, but by the value and need of certain fields of study. The courses offered should fit the need of the student and not the desire of the school.